SMOKING RESTRICTION LEGISLATION - DYER,DM (Tufts Archival Research Center, 2007)
Memo from Dennis Dyer to Rhode Island Tobacco Action Network volunteers regarding smoking restriction legislation. Urges volunteers to write to state Congress members. Includes list of members of the House, Health, Education and Welfare Committee, a list of suggested talking points, and a return envelope and legislative response form.